2015
DOI: 10.1387/ijdb.150192ao
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Sox genes in tooth development

Abstract: Members of the Sox gene family play roles in many biological processes including organogenesis. We carried out comparative in situ hybridization analysis of seventeen sox genes (Sox1-14, 17, 18, 21) during murine odontogenesis from the epithelial thickening to the cytodifferentiation stages. Localized expression of five Sox genes (Sox6, 9, 13, 14 and 21) was observed in tooth bud epithelium. Sox13 showed restricted expression in the primary enamel knots. At the early bell stage, three Sox genes (Sox8, 11, 17 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…3K), whereas in the Sox2 CreERT2/+ ; Ctnnb1 lox(ex3) embryos Sox9 was expressed in the forming successional tooth (Fig. 3L), in a similar pattern to that previously described for Sox9 at the cap stage (Kawasaki et al, 2015).…”
Section: Resultssupporting
confidence: 78%
“…3K), whereas in the Sox2 CreERT2/+ ; Ctnnb1 lox(ex3) embryos Sox9 was expressed in the forming successional tooth (Fig. 3L), in a similar pattern to that previously described for Sox9 at the cap stage (Kawasaki et al, 2015).…”
Section: Resultssupporting
confidence: 78%
“…In addition, it has been reported that the target genes of miR-499-5p in the anti-apoptosis process of myocardial cells may be PDCD4, calcineurin (CaN) and promoter protein-related protein-1 (Drp-1) (Chua et al 2016 ; Jia et al 2016 ; Wang et al 2011 ). SOX6 plays a crucial role in cell and organ development (Kawasaki et al 2015 ; Panman et al 2014 ). Studies have confirmed that miR-499-5p induced the up-regulation of type-I fiber number by inhibiting SOX6 (van Rooij et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…n/a n/a n/a n/a More detailed expression patterns for factors can be found in: (Kawasaki et al, 2015;Watanabe et al, 2016;Ishikawa et al, 2018). Epithelial (Epi), Mesenchymal (Mes), Muscle (Mus), Not expressed (n.e).…”
Section: G Sox15mentioning
confidence: 99%